Participatory Experiences as a New Way to Access Conservation Data in Museum Contexts - Veggi, Manuele; Pescarin, Sofia (Mimesis Journal, 2024)
The article explores the integration of participatory experiences in museum contexts to enhance access to conservation data. Following Simon’s principle of participatory museum, this contribution analyses the prototypes of two interactive experiences, BrancacciPOV and MyTISSE, developed in the framework of the research activity of CNR ISPC. The observation of the results of their evaluation sessions shows that both collaborative exploration in guided virtual tours and creative engagement are a possible answer to this research question.